Pengaruh Green Intellectual Capital, Komisaris Independen, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Trisna Putri Wijayaning Suri; Titik Aryati (Ikatan Da'i Indonesia, 2026)
This study aims to examine and analyze the effect of Green Intellectual Capital, Independent Commissioners, and Managerial Ownership on Firm Value in real estate and property companies listed on the Indonesia Stock Exchange during 2022–2024. This research used a quantitative method with secondary data obtained from annual reports and financial statements. The data were analyzed using panel data regression analysis. The results show that Green Intellectual Capital, Managerial Ownership, and Independent Commissioners have a positive and significant effect on Firm Value. This study is expected to provide references for companies and investors in improving firm value through environmental-based intellectual capital management and the implementation of good corporate governance.